Risk Factors for Incident Dementia Among Older Cubans - Geeske Peeters; Geeske Peeters; Arianna Almirall Sanchez; Arianna Almirall Sanchez; Jorge Llibre Guerra; Jorge Llibre Guerra; Jorge Llibre Guerra; Brian Lawlor; Brian Lawlor; Brian Lawlor; Rose Anne Kenny; Rose Anne Kenny; et al. (Frontiers Media S.A., 2020)
Introduction: Little is known about risk factors of dementia in Latin American countries. We aimed to identify socio-demographic, health and lifestyle risk factors of incident dementia in Cuban older adults.Methods: Data were from 1,846 participants in the Cuban cohort of the 10/66 Dementia Research Group. Participants completed questionnaires, health examinations, and cognitive tests at baseline (2003-2006) and 4.5 years later (2007-2010). Associations between risk factors (baseline) and incident dementia (follow-up) were examined using logistic regression.Results: Just over 9% of participants developed dementia. Overall, older age and low physical activity were associated with incident dementia. In those 65-74 years of age, depression, stroke and low physical activity were associated with incident dementia. In those ≥75 years of age, low physical activity, never eating fish, and smoking were associated with incident dementia.Conclusions: Modifiable lifestyle factors play an important role in developing dementia in Cuban older adults. This knowledge opens up opportunities for preventive strategies.